Pengaruh Penggunaan Media Audio Visual Terhadap Hasil Belajar Pkn Siswa Kelas V SDN No.15 Lantang Kecamatan Polombangkeng Selatan Kabupaten Takalar - Muh Ikbal; Andi Sugiati; Rismawati Rismawati (Harmoni Pendidikan : Jurnal Ilmu Pendidikan, 2024)
This research aims to determine the influence of the use of audio-visual media on the Civics learning outcomes of class V students. This type of research is pre-Experimental design research with a quantitative approach. The sample in this study was class V students at SDN No. 15 Lantang, Polombangkeng Sealatang District, Takalar Regency. The data in this study were analyzed using descriptive statistical analysis techniques and inferential statistics. The results showed that there was an influence of the use of audio-visual media on the Civics learning outcomes of class V students at SDN No. .15 Loud. This shows a descriptive statistical analysis of student learning outcomes using audio-visual media. Before using audio visual media there were 20 students or 95.23% who did not complete, only 1 student or 4.76% completed. After using audio visual media, 18 students or 85.71% completed, 3 students or 14.28% did not complete. Based on the results of the one sample t-test hypothesis test, the sig. (2-taillet) obtained 0.000 which shows that 0.000 < 0.5 or in other words H_0 is rejected and H_1 is accepted, which means that there is an influence of the use of audio-visual media on the Civics learning outcomes of class V students.